Colour-Specific Microfluidic Droplet Detection for Molecular Communication - Bartunik, Max; Fleischer, Marco; Haselmayr, Werner; Kirchner, Jens (Proceedings of the 7th ACM International Conference on Nanoscale Computing and Communication, 2020)
Droplet-based microfluidic systems are a promising platform for lab-on-a-chip (LoC) applications. These systems can also be used to enhance LoC applications with integrated droplet control information or for data transmission scenarios in the context of molecular communication. For both use-cases the detection and characterisation of droplets in small microfluidic channels is crucial. So far, only complex lab setups with restricted capabilities have been presented as detection devices. We present a new low-cost and portable droplet detector. The device is used to confidently distinguish between individual droplets in a droplet-based microfluidic system. Using on-off keying a 16-bit sequence is successfully transmitted for the first time with such a setup. Furthermore, the devices capabilities to characterise droplets regarding colour and size are demonstrated. Such an application of a spectral sensor in a microfluidic system presents new possibilities, such as colour-coded data transmission or analysis of droplet content.<br
Keywords: droplet detection; microfluidic environment; molecular communication; colour; optical sensor